SEASONAL VARIATION OF PHYSICO-CHEMICAL FEATURES OF WATER SAMPLED FROM TIGA RESERVOIR, NIGERIA - Elaigwu, A. M.; Okayi, R. G.; Tiamiyu, L. O. (FUDMA JOURNAL OF SCIENCES, 2023)
This study assessed the physico-chemical features and dissolved mineral elements of the water sampled from Tiga reservoir, Nigeria. The sampling period was between the months of May, 2014 to April, 2015, water samples were collected from a strategic point of effluent in cleaned bottles of average volume 250 ml. The physico-chemical and mineral elements were analysed in accordance to standard method using spectrophotometer. The results of the wet and dry seasons showed significant differences (p<0.05), total dissolved solids (77.08 mgl-1 and 54.88 mgl-1); turbidity (77.81 NTU and 34.01 NTU); chromium (0.02 mgl-1 and 0.01 mgl-1) and potassium (0.17 mgl-1 and 0.15 mgl-1). The mean values of biological oxygen demand (2.80 mgl-1); alkalinity (41.79 mgl-1); dissolved oxygen (7.05 mgl-1); calcium (0.15 mgl-1) and potassium (0.17 mgl-1), were within the recommended limits of European union (EU) and world health organisation (WHO) for aquatic life. Similarly, total dissolved solids (77.08 mgl-1); zinc (0.01 mgl-1); iron (0.15 mgl-1); chloride (6.67 mgl-1); sulphate (4.11 mgl-1) and nitrate (0.80 mgl-1) values stood within the limits recommended for drinking water by WHO. However, lead and cadmium were not detected. There were seasonal fluctuation of the water quality parameters. Also, it was a good appraisal of the water content on the basis of EU and WHO water quality standards. However, there was proof of contamination of the water sampled, as the BOD was high which suggest further survey to be conducted on regular basis in order to ascertain the condition of the water content in the reservoir.